Unethical Behavior's Moderating Effect on Managerial and Organizational Outcomes: Evidence from Public Hospitals. (2nd January 2020) - Rauh, Jonathan
Abstract : Unethical behavior affects both managerial and organizational outcomes. The direction of these effects is less well understood: Is there unethical behavior because of poor organizational outcomes, or are there poor organizational outcomes because of unethical behavior? By using data from public hospitals in the United States, this study provides evidence of a moderating effect in the relationship between managerial performance and organizational performance. Findings indicate that unethical behavior moderates the relationship between internal managerial outcomes and the organization's outcomes. This suggests that ethics are a conduit through which managerial outcomes are translated into organizational outcomes as opposed to being simply a quality of how that transfer takes place.